The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s40670-020-01114-9
|View full text |Cite
|
Sign up to set email alerts
|

Student Perspectives on Remote Medical Education in Clinical Core Clerkships During the COVID-19 Pandemic

Abstract: Purpose To assess student perceptions of remote learning curricula implemented by clinical clerkships at a single US medical school during the COVID-19 pandemic. Method Students enrolled in core clinical clerkships at the UC San Diego School of Medicine from March to April 2020 were sent an anonymous online survey, assessing components of remote learning curricula via quantitative rating and free-response questions. Results Of 132 students enrolled, 96 (73%) completed the survey. Online question banks, remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 24 publications
0
53
0
4
Order By: Relevance
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Practice guidelines [ 11 , 12 , 20 , 22 ] and training for faculty and students were provided [ 10 , 14 , 16 , 18 , 20 , 22 , 24 ] prior to encountering patients over the telehealth platform. In-advance informed consent from the patients were obtained and screening took place to ensure patients had the appropriate virtual interfaces [ 18 , 19 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct observation and participation in clinical care is a critical component of medical education, yet in response to the need to minimize infection exposure and enable social distancing, many medical students and other trainees were initially excluded from the clinical setting or thrust into new modalities of care that disrupted traditional clinical supervision practices. Creative deployment of telehealth technologies such as virtual rounds [ 79 ] and proctored telehealth visits [ 80 ] enabled trainees to safely rejoin clinical conversations and participate in clinical care [ 81 ]. Similarly, where appropriate, telehealth has also been recommended and deployed to enable the continued conduct of clinical trials while minimizing risks to participants [ 82 ].…”
Section: Telehealthmentioning
confidence: 99%
“…Students have responded positively to the adaptations to teaching and, mirroring the changes predicted by our respondents, want to continue with online lectures and increased access to online resources in the future. 39 It remains to be seen whether reactive adaptations implemented during the pandemic will be sustainable, and help to manage another impending challenge: the surge in student numbers resulting from the government temporarily lifting the cap on medical school places. 40 One year on from the first national lockdown, the course of the pandemic remains uncertain.…”
Section: A Call To Action In a Time Of Changementioning
confidence: 99%